2003
DOI: 10.1046/j.1365-2222.2003.01688.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mediator antagonism on mannitol and adenosine monophosphate challenges

Abstract: The dissociated effects of single doses of montelukast alone but not montelukast/desloratadine combination on AHR and recovery time, highlights the relative roles of histamine in initiating the bronchoconstrictor response and cysteinyl leukotrienes in sustaining it. Similar improvements in AHR and recovery time were observed following both indirect bronchoconstrictor stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 27 publications
3
37
1
Order By: Relevance
“…The gene expression, immunostaining in airway epithelial cells and bronchial macrophages, and the level of the sPLA 2 -X protein in the airways all increased in response to exercise challenge in the asthma group, whereas the levels remained constant after challenge in nonasthmatic control subjects. These results indicate that sPLA 2 -X may play a role in regulating the levels of proinflammatory eicosanoids in asthma, particularly in manifestations of indirect BHR, in which increased production of proinflammatory eicosanoids is critical (7)(8)(9).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The gene expression, immunostaining in airway epithelial cells and bronchial macrophages, and the level of the sPLA 2 -X protein in the airways all increased in response to exercise challenge in the asthma group, whereas the levels remained constant after challenge in nonasthmatic control subjects. These results indicate that sPLA 2 -X may play a role in regulating the levels of proinflammatory eicosanoids in asthma, particularly in manifestations of indirect BHR, in which increased production of proinflammatory eicosanoids is critical (7)(8)(9).…”
Section: Discussionmentioning
confidence: 97%
“…A major manifestation of asthma is exercise-induced bronchoconstriction (EIB), which reflects the degree of indirect bronchial hyperresponsiveness (BHR) (6). Dysregulated eicosanoid synthesis is prominent in indirect BHR (7)(8)(9). The levels of CysLTs in the airways, measured in exhaled breath condensate (10) or in induced sputum (11), are higher in patients with asthma with EIB than in patients with asthma without EIB.…”
mentioning
confidence: 99%
“…In other words, there was little difference between 1 and 4 weeks on BHR to methacholine. Indeed, even single doses of montelukast have been shown to attenuate BHR [21]. Asano et al evaluated the effects of pranlukast for 4 weeks in 48 patients with moderate-to-severe persistent asthma [20].…”
Section: Discussionmentioning
confidence: 99%
“…After exercise challenge, histamine and the mast cell protease tryptase are released into the airways, and inhibition of EIB with a cysLT 1 -receptor inhibitor plus an antihistamine reduced the amount of histamine released after exercise challenge [21]. In an analogous situation using mannitol challenge, pharmacologic inhibitors indicated that histamine was responsible for bronchoconstriction soon after challenge, whereas the release of cysLTs was responsible for sustained bronchoconstriction [28].…”
Section: Role Of Leukotrienes In the Pathophysiology Of Eibmentioning
confidence: 99%